THE ROLE OF INFORMATION AND ELECTRONIC TRANSACTIONS (ITE) LAW (LAW NO. 11 OF 2008) AND CYBER ETHICS: NURTURING POSITIVE BEHAVIOR IN THE CYBERSPACE ACCORDING TO PANCASILA FOR THE PEOPLE OF TANGERANG CITY - Arianto, Adi Rio; Indrawan, Jerry; Anggraini, Gesti; Setiawan, M. Chairil Akbar (Jurnal Pertahanan dan Bela Negara, 2020)
This paper aims to find out the factors behind the lack of awareness toward digital literacy and cyber ethics among the people of Tangerang City â€“ specifically, those who live in Neighborhood (RT 03) and Community Associations (RW 01) in Sandratex Street No. 106, Rempoa Urban Village, East Ciputat Sub-district, South Tangerang City, Banten Province, Indonesia. Digital literacy is related to the positive and negative impact of the internet. This paper employs a qualitative method and collects data through an interview and survey with forty people, which is consisted of 30 students, 5 Karang Taruna Rempoa activists, and 5 studentsâ€™ parents. This paper finds that the implementation of ITE Law has positively impacted the people of Tangerang through various means: first, the people of Tangerang City can make a contribution by becoming a social agent that can prevent and address online radicalism, hoax and online persecution in their neighborhood. This is possible because the ITE Law improves studentsâ€™ and the communityâ€™s cyber literacy significantly; second, the people of Tangerang City can understand about ethics and legal foundation through the socialization of â€œThe Role of ITE Law (Law No. 11 of 2008) and Cyber Ethicsâ€ as part of the efforts to prevent online radicalism, hoax and online persecution resulting from free access to the cyberspace; third, the people of Tangerang City can act upon the values of nationalism, national defense and Pancasila that are all contained within the ITE Law (Law No. 11 of 2008) in order to nurture positive behavior in the cyberspace; and fourth, the people of Tangerang City are more aware about the importance of cyber law and ethics in the cyberspace to control positive internet behavior and prevent the negative impact of the internet in all walks of life. Keywords: Cyber, Digital, Ethics, Information and Electronic Transactions (ITE) Law, Pancasila, Tangerang.